A interação dos usuários da UFMG com o catálogo on-line do Sistema Pergamum - Carla Cristina Vieira de Oliveira (2008)
The online catalogues, also known as Online Public Access Catalogue, changed the users routine, making possible simultaneous access to different resources by users in different places. It is important to research the form of interaction of university library users with the Pergamum Catalogue, since the majority of the user studies conducted so far have been developed among librarians and staff. This research analyses the interaction of users of the Pergamum Integrated Library System online catalogue, which is used by many universities in Brazil, in eight libraries of UFMGs library system. It also verifies the use of search resources and features available in the catalogue, shows the profile of users, verifies if the system has attends to some usability requirements listed in the literature and compares the differences and the similarities in the results for users in different fields of knowledge. This is a qualitative and descriptive research in which individual interview and critical incident techniques were used, in order to evaluate the catalogue from the endusers perspective. The study shows that users are satisfied with the Pergamum catalogue, although they do not use the many of the search resources available in the system. It was also observed that the users could be considered dynamic and demand effectiveness and speed. Browsing at the library stacks is very common among those users who do not show confidence in the use of the catalogue for subject searches. Regarding usability requirements, it was noticed that the system is considered not only satisfactory but also easy to learn and memorize by most of the students. Field of knowledge determine great differences among users. The users presented criticisms and suggestions about the Pergamum system, although they also recognized the importance of this information retrieval system and expect its improvement.